IMPLEMENTATION OF THE FAMILY HOPE PROGRAM PERMENSOS 1/2018 AL-MAWARDI'S PERSPECTIVE TANJUNG TIRAM SUBDISTRICT - Azhari, Imam; Pulungan, Sahmiar; BB, Putri Eka Ramadhani (Hukum tata Negara/Siyasah, 2025)
This research is a field study conducted in Tanjung Tiram sub-district, Batu Bara Regency. The research question in this study is how the implementation of Permensos No. 1 of 2018 concerning the Family Hope Program in Tanjung Tiram sub-district, Batu Bara Regency, what are the obstacles or challenges faced in the implementation process of Permensos No. 1 of 2018 concerning the Family Hope Program, how is the implementation of Permensos No. 1 of 2018 on the Family Hope Program is reviewed from the perspective of Imam al-Mawardi. In this study, the author identified the beneficiaries of the Family Hope Program as the research sample. In collecting data, the author used the following methods: observation, interviews, and documentation. The results of this study indicate that the reality of the implementation of the Family Hope Program in Tanjung Tiram District, Batu Bara Regency, is still inadequate. The Family Hope Program (PKH) facilitators in Tanjung Tiram District claim that the families receiving social assistance are the right targets and have never experienced any obstacles. However, after conducting interviews, researchers found that there were still many beneficiaries from the upper-middle class. This was because Penaping still did not pay enough attention to the coordination of the latest population census, activity planning, and the accuracy of services related to the Family Hope Program. From Imam Al-Mawardi's perspective, the implementation of the Family Hope Program in Tanjung Tiram Subdistrict is still far from successful. According to Imam Al-Mawardi, this is related to two institutions that play a role and are responsible, namely the wizarah and wazir. Therefore, the implementation of the Family Hope Program in Tanjung Tiram Subdistrict has not been fully carried out effectively because each institutional structure has not fully understood their roles and functions, and there is a lack of coordination between the wizarah Tanfidzh (the highest-ranking minister) and the wazir (as the implementing body under them), resulting in the program not being implemented to its full potential.Keywords: Implementation, Family Hope Program